Penerapan Model menara bola untuk Pembelajaran Efektif Pukulan Forehand Tenis Top Spin pada Mahasiswa Pendidikan Jasmani dan Kesehatan Unmus - Yambedoan, Thadius; Suhartini, Bernadeta; Nugroho, Arifin Ika; Wasa, Carolus; Hidayat, Afif Khoirul; Rismayanthi, Cerika (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
ABSTRAK This study aims to evaluate the application of the ball tower model in learning forehand top spin shot techniques for students of the Physical Education, Health and Recreation Department of Unmus. The research identified four main indicators of problems, namely: lack of effective tools; low student confidence; lack of constructive feedback from the instructor, and  the importance of considering variations in student learning styles. The results showed that limited tools and practice time had a negative impact on students' ability to practice optimally. In addition, students' low confidence was caused by uncertainty in applying techniques and lack of support from instructors. Unspecific feedback also caused confusion in understanding the correct technique. This study recommends corrective measures, including providing adequate tools, increasing instructor support, and paying more attention to students' learning styles to create an inclusive and effective learning environment. The application of the ball tower model in learning forehand top spin strokes for Penjaskesrek Unmus students shows that several significant obstacles need to be overcome to increase the effectiveness of the learning process.